2019
DOI: 10.3390/ijms20194710
|View full text |Cite
|
Sign up to set email alerts
|

Immunomonitoring of Tacrolimus in Healthy Volunteers: The First Step from PK- to PD-Based Therapeutic Drug Monitoring?

Abstract: Therapeutic drug monitoring is routinely performed to maintain optimal tacrolimus concentrations in kidney transplant recipients. Nonetheless, toxicity and rejection still occur within an acceptable concentration-range. To have a better understanding of the relationship between tacrolimus dose, tacrolimus concentration, and its effect on the target cell, we developed functional immune tests for the quantification of the tacrolimus effect. Twelve healthy volunteers received a single dose of tacrolimus, after wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
2
12
3
Order By: Relevance
“…Finally, it is possible that both whole‐blood and intracellular tacrolimus concentrations are not the right matrix for monitoring tacrolimus exposure. Future studies may also focus on other matrices to monitor tacrolimus treatment, which might have a stronger correlation with clinical outcomes, such as for example, the T lymphocyte subset of PBMCs or the unbound (or free) tacrolimus concentrations 2,46–48 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is possible that both whole‐blood and intracellular tacrolimus concentrations are not the right matrix for monitoring tacrolimus exposure. Future studies may also focus on other matrices to monitor tacrolimus treatment, which might have a stronger correlation with clinical outcomes, such as for example, the T lymphocyte subset of PBMCs or the unbound (or free) tacrolimus concentrations 2,46–48 …”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies that reported a poor correlation between TAC [PBMC] and whole-blood C 0 . [6][7][8][9][10][20][21][22] The poor correlation between whole-blood C 0 and intracellular tacrolimus concentrations emphasizes the importance of measuring tacrolimus concentration in its target compartment(s), as the latter cannot be extrapolated from whole-blood concentration.…”
Section: Discussionmentioning
confidence: 99%
“…time of transplantation, % (median, Q1-Q3) 0 (0-4) Time from transplantation to kidney biopsy, days (median, Q1-Q3) 9(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) ESRD, end-stage renal disease; HLA, human leukocyte antigen; PRA, panel reactive antibody.…”
mentioning
confidence: 99%
“…Many animal models and in vitro studies describe IST effects, but few studies detail effects of in vivo chronic posttransplant IST exposure on human PBMC 3,32,46,50,54,55,72‐75 57–64 …”
Section: Discussionmentioning
confidence: 99%